2021
DOI: 10.1016/j.infsof.2021.106586
|View full text |Cite
|
Sign up to set email alerts
|

Insights on the relationship between decision-making style and personality in software engineering

Abstract: Software development involves many activities, and decision making is an essential one. Various factors can impact a decision-making process, and by understanding such factors, one can improve the process. Since people are the ones making decisions, some human-related aspects are amongst those influencing factors. One such aspect is the decision maker's personality.Objective: This research investigates the relationship between decision-making style and personality within the context of software project develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…They collected personality proiles of 182 software practitioners using IPIP test. 45.1% of them were software testers and the majority of the rest were programmers. The results indicate that software testers are higher on conscientiousness factor than other software practitioners.…”
Section: Human Aspects In Sotware Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…They collected personality proiles of 182 software practitioners using IPIP test. 45.1% of them were software testers and the majority of the rest were programmers. The results indicate that software testers are higher on conscientiousness factor than other software practitioners.…”
Section: Human Aspects In Sotware Engineeringmentioning
confidence: 99%
“…Mendes et al [45] conducted a study investigating the relationship between decision-making style and personality within the context of software project development where they conducted a survey and collected data from 63 software engineers. They identiied seven statistically signiicant correlations between decision-making style and personality and built a regression model considering the decision-making style as the response variable and personality factors as independent variables.…”
Section: Human Aspects In Sotware Engineeringmentioning
confidence: 99%
“…Through regression analysis, they uncovered a strong link between neuroticism and burnout. Mendes et al [75] surveyed 63 Brazilian developers and found that the agreeableness trait is signiicantly associated with the variation in the decision-making style. Smith et al [111] analyzed the characteristics of professional developers' personalities based on their roles.…”
Section: Personality Detection In Sotware Engineeringmentioning
confidence: 99%
“…Through regression analysis, they uncovered a strong link between neuroticism and burnout. Mendes et al [75] surveyed 63 Brazilian developers and found that the agreeableness trait is significantly associated with the variation in the decision-making style. Smith et al [111] analyzed the characteristics of professional developers' personalities based on their roles.…”
Section: Personality Detection In Software Engineeringmentioning
confidence: 99%